Effects of Environmental Gradients on the Biomass of Alien Cercopagis pengoi in the Neva Estuary - Golubkov, Mikhail S.; Litvinchuk, Larisa F.; Golubkov, Sergey M. (Frontiers in Marine Science, 2020)
Biological invasions are a global trend due to globalization of the world. An important goal of invasion biology is to identify environmental characteristics that may make a region receptive to invasions. We tested the hypothesis that environmental variables have stronger effect on the biomass of the alien Cercopagis pengoi in the Neva Estuary than biotic interactions with other zooplankton species. Hierarchical cluster, principal component and Pearson correlation analyzes were used to elucidate changes within the zooplankton community along environmental gradients. The data analysis showed that the biomass of C. pengoi was higher in waters with higher salinity, low temperature, high transparency, lower chlorophyll a concentration and lower proportion of chlorophyll in particulate suspended matter. The biomass of C. pengoi showed significant positive correlations with biomasses of its potential preys. However, we did not find direct significant negative correlations between C. pengoi and larger zooplankton predators Leptodora kindtii and Bythotrephes spp. This research generally supports the hypothesis that if environmental variables are appropriate for an exotic species, then that species is likely to invade successfully, regardless of the native species already present.